zum Directory-modus

Grundlegende Differenziationsregeln

Quotientenregel

Theorem
Ein Quotient zweier Funktionen lässt sich nach der Quotientenregel differenzieren.
f ( x ) = u ( x ) v ( x ) f ' ( x ) = u ' ( x ) v ( x ) - u ( x ) v ' ( x ) [ v ( x ) ] 2
Beispiel

Differenziere

f ( x ) = x 2 + 1 2 x 3 + 4 .

Laut der Quotientenregel ist

f ' ( x ) = d d x ( x 2 + 1 ) ( 2 x 3 + 4 ) - ( x 2 + 1 ) d d x ( 2 x 3 + 4 ) ( 2 x 3 + 4 ) 2 = 2 x ( 2 x 3 + 4 ) - ( x 2 + 1 ) 6 x ( 2 x 3 + 4 ) 2 = 4 x 4 - 6 x 3 + 2 x ( 2 x 3 + 4 ) 2 .
Seite 8 von 13